Imobilização e estabilização de β-galactosidase por ligações multipontuais em Duolite A568 - Falleiros, Larissa Nayhara Soares Santana (2012)
β-galactosidase has presented increased use in the dairy industry, since it can be used to produce a isomolecular mixture of glucose and galactose and also has wide application in biotechnological production of milk with a low-lactose content and in production of galactooligosaccharides from whey lactose, which is abundantly available as a byproduct of the dairy industry. Having a great interest in the stabilization by multipoint covalent attachment of the enzyme immobilized, since these bonds can increase stiffness of the enzyme and, therefore, increase the stability against inactivating agents. In this work was studied the immobilization and stabilization of β-galactosidase using as carrier the ion exchange resin Duolite A568, with and without cross-linking using glutaraldehyde. The immobilization process was constituted by adsorption of the enzyme in Duolite A-568 and the stabilization procedure was performed by incubation of the biocatalyst in buffer pH 9 at 25 ° C ± 1 ° C for 24h. Was evaluated the influence of the steps s order to obtain the immobilized biocatalyst, as well as the influence of buffer used and the presence of the substrate in the process of obtaining biocatalyst. The stability of the biocatalyst obtained was evaluated with respect to pH, temperature and storage. The immobilized enzyme was packed in a fixed bed reactor with recycle operating in continuous, in order to assess the hydrolysis process this type of reactor as a function of recycle ratio used. Was studied the operational stability of the biocatalyst during 800 residence time in the reactor. The results indicated that the production s method to immobilize β-galactosidase from Aspergillus oryzae on Duolite A568 which improvement the catalytic activity was the result of the immobilization process by adsorption, followed by stabilization step, and finally subjected to the process of cross-linking with glutaraldehyde, promoting an increase of 44% enzyme activity compared with the activity achieved by the biocatalyst obtained by the processes of adsorption and cross-linking. The use of borate buffer reduced the activity by approximately 70% compared with the activity obtained by using phosphate buffer. The addition of lactose as a protective compound the active site of the enzyme during immobilization did not alter the performance of the biocatalyst, showing that the active site is not directly involved in the process of immobilization. The biocatalyst obtained by the combination of adsorption processes, stabilization, and crosslinking was highly stable over the entire pH range studied. It was observed a strong dependence of the immobilized enzyme in relation to temperature. At temperatures of 60, 57,5 and 55 °C there was a level of stability to the 30 minutes of incubation, from there one can observe the thermal inactivation process. At 55 °C after 140 minutes, the biocatalyst retained 77% its activity relative to baseline.The model of thermal deactivation of the first order was the best fit to the experimental results to describe the kinetics of thermal deactivation of the immobilized enzyme. The activation energy of thermal deactivation process of β- galactosidase from Aspergillus oryzae immobilized was 71,03 kcal/mol with half-lives of 5,5 hours at 55 °C. The immobilized enzyme retained its activity after 100 days of storage in acetate buffer pH 4.5 at 4 ± 2 ° C. The recycle ratio of 0,5 promoted an increase of approximately 40% of the overall conversion as compared to the conversion per pass achieved for the same operating condition.